A rare case report of perosomus elumbis with concurrent visceral abnormalities in a jersey cross bred calf - R. Siva Shankar; M. Gokulakrishnan; M.S. Sabarish Babu; S. Dinesh Kumar; Viji Vijayan; Ravi Sundar George (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A day old calf was presented to Large Animal Clinic-Out Patient (LAC-OP) unit of Madras Veterinary College Teaching Hospital with the history of constipation and unable to defecate since birth. On the physical examination there was atresia ani, recto-vaginal fistula (Fig: 1) and angular limb deformities, and distended abdomen. Plain radiography of abdomen lateral view was taken, which was confirmed as Perosomus Elumbis (PE) anomaly.